ANALISIS DAYA SAING EKSPOR UBIKAYU INDONESIA - Putri Suci Asriani (Agroland: Jurnal Ilmu-ilmu Pertanian, 2011)
Cassava (Manihot Esculenta Crantz) is one of the export commodities from food crops sub-sectorand has potency to be developed. Indonesia is the biggest fourth producer of cassava in the worldafter Nigeria, Brazil and Thailand. Cassava grows very well under limited rainfall and poor soilconditions, with flexibility in planting and harvesting period. However, the negative impact andimage of cassava cause existing potency cannot be improved optimally, either in export or domesticmarket. This research aimed to identify level of comparative advantage and competitive position forthe Indonesian cassava products. Revealed Comparative Advantage (RCA), SpecializationCommerce Index (SCI), and Acceleration Ratio (AR) analysis were implemented to determine thecompetitiveness rate of Indonesian cassava. The result of analysis will be used as the basicdeterminant of Indonesian cassava export and domestic market potencies. The results of theresearch showed that Indonesia has a strong comparative advantage for the commodities of cassavaand tends to be net exporter.Key words : Cassava, competitiveness, export market, domestic market.